Beginning L2 complexity development in CLIL and non-CLIL secondary education. Issue 2 (1st November 2019) - Bulte, Bram; Housen, Alex
Abstract : The present study analyses the impact of a bilingual Content and Language Integrated Learning (CLIL) programme vis-à-vis a regular monolingual programme on the development of different aspects of L2 learners' linguistic (syntactic, morphological and lexical) complexity. Five pupils enrolled in a Dutch–English CLIL programme in a secondary school in the Netherlands are compared with five peers following the mainstream programme with English as a Foreign Language (EFL) teaching. The longitudinal development of these ten pupils' linguistic complexity in L2-English is investigated by means of six complexity measures calculated for each of eleven writing tasks collected over a period spanning their first nineteen months of secondary education. Linear mixed models are used to estimate the effects of time and programme type on the pupils' L2 complexity. The results indicate that both groups of learners significantly increase the complexity of their L2 writing over the course of the study. Surprisingly, only limited effects of programme type (CLIL vs non-CLIL) are found, despite considerable differences in the quantity and quality of instructional exposure to the target language, suggesting that for these pupils increased and more varied instructional exposure to the L2 in the CLIL programme did not lead to significantly different L2 productions in terms of linguistic complexity. Several possible explanations for these findings are considered and the implications for CLIL research are discussed.